Influence of Meteorological Conditions on Effectiveness of Acoustic Screens – Measurements and Computations - RUDNO–RUDZIŃSKA, Barbara; MALEC, Tomasz; SAWA, Łukasz (Archives of Acoustics, 2008)
The paper presents the results of simulation and field studies of the effectiveness of roadacoustic screens. In the simulation studies the influence of the declared weather conditionson the predicted acoustic screen effectiveness determined for different field conditions bydifferent methods is analyzed. A comparative analysis of the results of screen effectivenesscomputations and measurements for three real systems of acoustic screens located by nationalroads in urbanized areas for different times of day is made.